Effect of Rubric-Based Feedback on the Writing Skills of High School Graders - Ali Alsagheer Abdelal Hasan (Yayasan Keluarga Guru Mandiri, 2022)
This study aimed at exploring the impact of utilizing rubric based feedback on developing the EFL writing skills of Saudi high school students. This study recruited 65 students of the second semester of high school students during the academic year 2019. The experimental group consisted of 31 students, who utilized the rubric based feedback during their writing instruction, while the control group comprised 34 students, who were taught in a traditional way in the classroom. Paired t-test revealed that there was a significant difference between mean scores of both the experimental and control group participants favoring the experimental group participants; confirming the positive impact of utilizing rubric based feedback on developing Saudi high school students' writing skills. These findings have provided evidence that the rubric based feedback has effectiveness in developing the writing skills of Saudi high school students